Clinicians’ perspectives of health related quality of life and priorities in deciding management for malignant pleural effusion - Sivakumar, P; Curley, D; Rahman, N; Lee, Y; Feller-Kopman, D; West, A; Ahmed, L (BMJ Publishing Group, 2016)
The management of malignant pleural effusion (MPE) has dramatically changed in the last decade with the increasing use of indwelling pleural catheters (IPC) and thoracoscopy. Although treatment is primarily aimed at improving health related quality of life (HRQOL), data on outcomes is limited, with management guided by clinician perspectives and experiences.